Two new species of Ooia (Araceae) from Sabah, Malaysian Borneo - Kartini Saibeh (University of Florence, 2023)
Two new species of Ooia (Araceae) from Sabah, Malaysia, Ooia sayapensis Kartini and Ooia ulusenagangensis Kartini are described as new species. Both are distinguished from the only current Sabahan species, Ooia kinabaluensis (Bogner) S.Y. Wong & P.C. Boyce by the presence of pistillodes at the pistillate flower zone.